Comparative Analysis of the Level of Liberality of the Banking System Across Countries - Orkhan Sultanov (HM Journals, 2022)
The main goal of the study is the creation of an economic model - an index that allows measuring the level of public intervention in the banking system at the global level, taking into account the characteristics of the latest prudential innovations and changes at the modern stage. The regulatory instruments that allow the central banks to conduct regulation in the monetary sphere and which can be fully or partially determined by the central banks have been taken as the aim of the study. The subject of the study is the measurement of government intervention or regulatory intervention in the banking sector.